Peningkatan Kualitas Kemasan Produk Untuk Meningkatkan Omzet Penjualan Macaroni Goreng Cap Ikan di Masa Pandemi Covid-19 - Roni Alim Ba’diya Kusufa; Ika Meviana; Riril Mardiana Firdaus (STIE Malangkucecwara, 2022)
Macaroni Cap Ikan, is the most widely known macaroni snack in the Malang market. Many UMKM market macaroni in various regions and have opened branches everywhere. It is often found in the market that macaroni packaging is less attractive and is only labeled in the form of photocopied paper, there is no particular brand that characterizes it. Therefore, it is necessary to manufacture macaroni packaging that is labeled attractively and becomes the hallmark of the brand. with the existence of a quality brand of macaroni, it is hoped that the macaroni will be easily recognized by the wider community. The purpose of this service is to improve the quality of product packaging and expand marketing. The methods offered are: 1) Packaging: (a) training and mentoring as well as improving the quality of Fried Macaroni packaging IkanCap Ikan with labels made from Bontaq stickers so that the packaging is more attractive and quality (b) Training and mentoring as well as procurement of electric sealer tools for Fried Macaroni packaging Ikan Cap Ikan Cap so that the packaging doesn't leak easily. 2) marketing: training and marketing assistance through online media by creating websites, Instagram, Facebook and WhatsApp groups to increase sales turnover of fried macaroni Cap Ikan.